ESTIMATING THE CROP COEFFICIENT FOR CROPS CULTIVATED IN UPSTREAM AREA OF XUAN HUONG LAKE, DALAT CITY - Nguyễn Thị Thanh Thuận; Chế Đình Lý; Hồ Thị Hằng (Tạp chí Khoa học Đại học Đà Lạt)
Applying Lysimeter method combined with CROPWAT model, crop coefficient of two types of vegetables (cabbage and Chinese cabbage) and three types of flowers (chrysanthemum, lily, and lisianthus) cultivated in the upstream area of Xuan Huong lake, Dalat city has been identified. Among the researched plants, the Chinese cabbage has the lowest coefficients of crops in all three initial, middle, and late crop seasons (respectively, 0.3, 1.25, and 0.81). A crop coefficient of Chrysanthemum is the largest in the middle stage (Kcmid = 1.4), followed by cabbage (Kcmid = 1.3). Kcmid of Chinese cabbage, Lily, and Lisianthus are approximately the same (respectively 1.25, 1.27, and 1.25). The chrysanthemum still has the large water demand in the final stage, it was reflected in Kcend = 1.07, followed by lily (1.05) and lisianthus (1.00) while Chinenes cabbage and cabbage in this stage is only at 0.81 and 0.93. It can be explained about this difference that because flowers still need a lot of water to provide for the flowering process and evaporation of leaves. When a crop coefficient is available, the calculation of water demand will become extremely simple through the correlation equation between the crop coefficient (Kc), the actual evapotranspiration (ETc), and the reference evapotranspiration (ETo). Therefore, we can have an effective irrigation plan and a better irrigation water management.